Прогноз диэлектрических потерь в стеклокерамике для разных соотношений массовых долей компонентов - Dmitriev, M. V.; Yerimichoy, I. N.; Panov, L. I. (PE "Politekhperiodika", Book and Journal Publishers, 2012)
An engineering method for predicting the dielectric loss in two-component non-porous glass ceramic has been proposed. The method allows to reduce the time and expense for conducting experiments and calculations during the design of such glass ceramic.